Multiple Fourier Sums on Sets of $\bar ψ$ -Differentiable Functions (Low Smoothness) - Lasuriya, R. A. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We investigate the behavior of deviations of rectangular partial Fourier sums on sets of $\bar ψ$-differentiable functions of many variables.